In vivo and In vitro Oxidative Stress Studies of Membrane Alterations (Fluidity and Permeability) in Mammalian Red Blood Cells - Giuseppe Gallo (Innovations in Biological Science Vol. 10, 2024)
Objectives: The purpose of this study was to evaluate the ability of vitamin E and polyphenols (red wine polyphenols, resveratrol, and catechin) on fluidity (fluorescence anisotropy) and anion permeability for chloride of membrane on mammalian erythrocytes respectively exposed to the water-soluble free radical initiator 2.2’-azobis-2 amidinopropan dihydrochloride (AAPH) and trained horses. Methods: The animals were ten Arabian strain horses, 6-8 years old, trained for Cross country, and six horses at rest. Membranes are tested for diphenylhexatriene fluorescence anisotropy in red blood cell membranes by Perrin plot. The reducing agent treatment efficacy was observed by the evaluation of anion permeability for chloride in red blood cells (RBCs). Anion permeability for chloride is an indicator of membrane protein damage and is evaluated in RBCs by the specific absorption of methemoglobin (CM) at 590 and 635 nm after treatment of heparinized blood with NaNO2. Results: Fluorescence anisotropy is abruptly worsened in erythrocyte membranes from exercised animals and almost restored after vitamin E treatment of membrane preparations and P > 0.05 by ANOVA. Polyphenol treatment is associated with a significant increase in anion permeability for chloride compared with control and AAPH-affected cells. Discussion: Fluorescence anisotropy is abruptly worsened in erythrocyte membranes from exercised animals and almost restored after vitamin E treatment of membrane preparations. In this study, it is evident that after In vitro oxidative damage of the membrane, red wine polyphenol extracts act as effective reducing agents and also as a CM indicator of membrane protein damage. Consequently, both red wine and polyphenol extracts both alone and mixed among them efficiently relieve the effects of oxidative stress.